Research Assessment and Legal Scholarship - Christopher Arup (Legal Education Review)
This paper pursues some related, interdisciplinary themes relevant to the future of law and the teaching of law. In part, it responds to recent contributions by Margaret Thornton and by Tamara Walsh. The major argument is that while positivism in the social sciences (such as psychology) is of historical interest only, positivism in legal studies remains distinct and valid. Even if it seems paradoxical, in emphasising the conventional (that is, socially constructed) nature of legal regulations and obligations, legal positivism is entirely consistent with the post-positivist trends in social science. It is capable of carrying forward the impulse of critical legal studies and helping to shape the critical pedagogy that may currently be lacking within legal education.